A new nonlinear extended state observer design for output tracking of uncertain nonlinear systems. Issue 2 (14th September 2020) - Zhao, Zhi‐Liang; Ma, Pengjuan; Chen, Sen
Summary: In this article, we develop a new nonlinear extended state observer (ESO) for output tracking of a class of uncertain nonlinear affine systems. Instead of using the linear functions of the error, the nonlinear functions of the properly magnified error are used in the proposed ESO. Compared with the linear ESO, the new ESO allows more accurate estimation and smaller peaking value. We also design an output‐feedback controller based on the proposed nonlinear ESO. The convergence of the new ESO is proved without assuming the boundedness of the system state. It is also proved that under the proposed output‐feedback controller, the system output is capable to track the given reference signal despite a large scope of nonlinear uncertainties. Simulation results illustrate the effectiveness of the new ESO with improved performance. Abstract : A new nonlinear extended state observer (ESO) for output tracking of a class of uncertain nonlinear affine systems is developed. Instead of using the linear functions of the error, the nonlinear functions of the properly magnified error are used in the proposed ESO, which can allow more accurate estimation and smaller peaking value. Despite a large scope of nonlinear uncertainties, the convergence of the ESO and the satisfied tracking performance is investigated without assuming the boundedness of the system state.